The importance of BUD13 in the prognosis of hepatocellular carcinoma revealed by pan-cancer analysis: BUD13 in the prognosis of hepatocellular carcinoma - He, Han; Qiu, Zhiyuan (Cellular and Molecular Biology, 2023)
RNA splicing is an essential process involved in many aspects of cell proliferation, survival and differentiation, and given the importance of RNA splicing in gene regulation, alterations in this biological behavior have been associated with many human cancers. BUD13 as an RNA binding protein (RBP) has been sparsely studied in tumors; consequently, there is a compelling need to further investigate the expression profile of BUD13 in human cancers to provide new molecular clues for the pathogenesis of hepatocellular carcinoma. For this porpuse, we used a series of bioinformatics methods to synthesize the relationship between BUD13 and prognosis, tumor microenvironment (TME), immune infiltration, tumor mutational load (TMB), and microsatellite instability (MSI), and tried to find the potential biological processes of BUD13 in tumors by GSEA and GSVA. And the association between the expression of BUD13 gene and prognosis was predicted by constructing a nomogram of hepatocellular carcinoma by multifactorial regression model. Results showed tgat in the present study, we found that elevated expression of BUD13 is associated with poorer OS in a numerous cancers, including ACC, KIRC, LGG, LIHC, READ, THYM, and UCS.More importantly, BUD13 expression levels were also significantly correlated with TME. Our results also indicated that BUD13 expression was closely associated with Pyroptosis genes and immune-related genes. Furthermore, BUD13 expression was associated with TMB, MSI and antitumor drug sensitivity in various cancer types. Functional bioinformatics analysis indicated that BUD13 may be involved in multiple signaling pathways and biological processes in hepatocellular carcinoma. Based on BUD13 expression, a risk factor model was found to predict OS in hepatocellular carcinoma. In conclusion, overall this study suggests that BUD13 expression is associated with poor prognosis and may be involved in the development and progression of hepatocellular carcinoma, which may be further explored as a potential prognostic marker and new targeted therapy.